Dynamic recrystallization and mechanical behavior of Mg alloy AZ31: Constraints from tensile tests with in-situ EBSD analysis - Boissonneau, Gaëtan; Tommasi, Andréa; Barou, Fabrice; Lopez-Sanchez, Marco Antonio; Montagnat, Maurine (Comptes Rendus. Mécanique)
We conducted tensile tests on Mg AZ31 samples with in-situ EBSD acquisition at 250°C and 10-3 s-1 to characterize the evolution of dynamic recrystallization (DRX) and its effect on the mechanical behavior. To investigate the entire deformation range up to failure at 65-67% engineering strain, step-wise experiments were conducted with in-situ EBSD acquisition at 2-5% strain intervals. Both in-situ microstructural observations and statistical analysis of microstructural properties document continuous DRX with nucleation by association of bulging and subgrain rotation starting at strains as low as 6%. However, the microstructure evolves slowly, mainly by development of substructure (polygonization), with DRX limited to isolated clusters, until 35% strain. This long incubation period is followed by acceleration of DRX, with faster grain boundary migration allowing for development of a DRX-necklace structure, whose spatial heterogeneity controls the final strain localization at strains > 60%. The microstructural evolution contrasts with the bulk mechanical behavior, which displays a linear decrease in the hardening rate between 15 and 60% strain. Comparison of the observed texture evolution with predictions by polycrystal plasticity simulations without DRX shows that DRX-induced changes in texture counteract the geometrical hardening due to the texture evolution resulting from dislocation glide. Microstructural softening is, nevertheless, required to compensate for hardening due to increase in the dislocation density. The intensity of this softening has to steadily increase with strain to explain the decrease in hardening rate between 15% and 60% strain. The apparent discrepancy between the kinetics of the microstructural evolution and the mechanical behavior implies, however, that the bulk softening does not depend solely on the DRX volume fraction, but also on its spatial organization.